Contextualization of the theory of business - V. V. Biryukov; E. V. Romanenko (Вестник СибАДИ)
In article questions of a kontekstualization of the theory of business are considered. The specified methodology allowing to offer complete vision of a solution of the problem of research of plurality of contexts and their influence on businesses, and also influences of business on contexts is proved. Multicontextual approach which is focused on the revalentny description of processes of structuring business activity and identification of the mechanisms of this structuring arising in concrete historical conditions is presented. For research of plurality of contexts it is offered to use multidimensional system of the coordinates expressing a projection (context) of the major structural conditions of business.